Enhancement of antifouling properties using rice husk silica particles in polysulfone membrane and optimization of its operating condition - Jamalludin, Mohd Riduan (2014)
This study investigates the effects of rice husk silica (RHS) as additive in the polysulfone membrane to enhance antifouling properties in membrane separation process. The flat sheet PSf/RHS membrane was prepared via phase inversion technique. The characterization and performance test were conducted on PSf ultrafiltration membrane prepared from a different additive concentration. The thermal stability of prepared membrane was observed by using thermogravimetric analysis (TGA). The cross section area and particles distribution of additive were carried out by using the scanning electron microscope (SEM) while the surface morphology was investigated via field emission scanning electron microscope (FESEM). The surface roughness and hydrophilicity were also determined by using Atomic force microscopy (AFM) and contact angle measurement respectively. Meanwhile, the performance was evaluated in term of pure water flux (PWF), rejection and antifouling properties. The optimized of normalized flux (Jf /Jo) at different parameter filtration condition (pH, ionic strength and tranmembranepressure) was carried out by using the response surface methodology (RSM).